TRANSLATION OF RELIGIOUS-CULTURAL TERMS OF ADDRESS IN THE LUKE’S BIBLE - I Made Brata, Frans; Putra Yadnya, I. B.; Sutjaja, I Gusti Made; Meko Mbete, Aron (e-Journal of Linguistics; Vol. 4. Juli 2010 No. 2, 2010)
This study analyses words and phrases used for addressing in the translation ofreligious-cultural terms of address in the Luke’s Bible. Their profiles and attitudes,techniques, methods, and ideologies applied as well as factors leading to and theirimpacts towards the degree of accuracy, readability, and acceptability were qualitativelydescribed.The data were taken from the Luke’s English Bible and their translations intoBalinese. First, the terms of address found in the source text were compared with thosefound in the target text with reference to the appraisal theoretical framework to identifythe social stratifications to which the addressee belongs to, which was then applied toidentify what translation techniques were applied. The formal and dynamic equivalence(de Ward and Nida, 1986: 36), and V diagram of the translation method (New Mark,1988: 45) were employed to show the translation orientations closely related to thetranslation ideology itself.The findings show that: (1) the choice of the linguistic variants in the targetlanguage was influenced by the dimensions of attitude: affect, judgment, andappreciation, either (positive [+], or negative [-]) among the participants; (2) there were12 translation techniques applied, two of which were the technique of calque and literal(0.06%) which were oriented towards the source language, 0.02% was ‘gray’, and therest, that is, 99.2% was oriented towards the target language. The dominance of thetranslation techniques which were oriented towards the target language shows that therewas a great cultural difference between the source text and the target text; (3) thedominance of the translation communicative method and the domestication ideologyshows that, when the translation process took place, the translator’s orientation wastowards the target reader; (4) the linguistic factor, the religious-cultural difference, andthe translator’s preference led to the translation techniques, methods and ideologiesapplied to translating the terms of address in the Luke’s Bible; (5) the translationtechniques, methods, and ideologies employed, positively contributed to the quality of thetranslation, causing the translation product to be highly accurate, intelligible, andculturally acceptable to the target reader.
Keywords: attitude, translation techniques, methods, ideology